PENGARUH KEBIJAKAN PENDANAAN, KEBIJAKAN INVESTASI, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN RISIKO BISNIS SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan yang tergabung dalam Indeks LQ45 2011-2015) - Reza Zulfikar Alza, A.A Gde Satia Utama (Universitas Airlangga, 2018)
Risk is an integral part of the company's policy considerations. risks can affect the implications of a policy, so measurement and calculation of the effects of risk are required to develop appropriate policies. this study aims to examine whether there is an influence between the policy made by managers in terms of funding, investment, and dividend distribution of corporate value by considering the business risk factors facing the company.The samples of this study are public listed company which listed on the bei in the lq 45 index in a row from 2010-2015. in this study used 16 samples each year during the period of observation, and hypothesis test by using multiple linear regression method.the results of this study indicate that (1) the funding policy has a positive and significant influence on firm value, and business risk moderates the interaction of the effect of funding policy on firm value (2) investment policy has positive and significant influence on firm value, and business risk strengthens the policy relationship investment in corporate value (3) dividend policy has no effect on firm value and business risk does not moderate the effect of dividend policy on firm value. The results of this study contribute to potential investors to be used as a reference for the policy decided by the manager so as to minimize the risks that may occur.